Does the Implant Surgical Technique Affect the Primary and/or Secondary Stability of Dental Implants? A Systematic Review - Rola Muhammed Shadid; Nasrin Rushdi Sadaqah; Sahar Abdo Othman (Hindawi Limited, 2014)
Background. A number of surgical techniques for implant site preparation have been advocated to enhance the implant of primary and secondary stability. However, there is insufficient scientific evidence to support the association between the surgical technique and implant stability. Purpose. This review aimed to investigate the influence of different surgical techniques including the undersized drilling, the osteotome, the piezosurgery, the flapless procedure, and the bone stimulation by low-level laser therapy on the primary and/or secondary stability of dental implants. Materials and methods. A search of PubMed, Cochrane Library, and grey literature was performed. The inclusion criteria comprised observational clinical studies and randomized controlled trials (RCTs) conducted in patients who received dental implants for rehabilitation, studies that evaluated the association between the surgical technique and the implant primary and/or secondary stability. The articles selected were carefully read and classified as low, moderate, and high methodological quality and data of interest were tabulated. Results. Eight clinical studies were included then they were classified as moderate or high methodological quality and control of bias. Conclusions. There is a weak evidence suggesting that any of previously mentioned surgical techniques could influence the primary and/or secondary implant stability.